2021
DOI: 10.12688/f1000research.51400.1
|View full text |Cite
|
Sign up to set email alerts
|

Scientific research and innovation response to the COVID-19 pandemic in Peru

Abstract: Background: COVID-19 has shaken countries at all levels, putting public health at risk. Global efforts have allocated funding for the development of research for the development of vaccines, digital tools, epidemiologic, social, and economic studies. Although these efforts have been developed worldwide, not all countries have prioritized the same topics, and may have a different impact on solving problems and containing the spread of COVID-19. Methods: A descriptive study was conducted with secondary data of "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…However, it has been shown that there are limitations in the use of English among students and teachers of health sciences, which is a limitation in scientific production, which to some extent may also be a factor that reduces the increase in scientific production [25]. More studies are needed to understand the effects of language on scientific production in Scopus as well as the resources and funding of scientific projects that end up in publication [26]. Our results also show international scientific collaboration, where there are usually formal collaborations in which the institutions or countries sign agreements highlighting the benefits and responsibilities of the study in question; at the same time, there are also informal collaborations, where the scientists involved share all or part of the information, as well as the materials and training necessary to carry out the study [13,14,16].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that there are limitations in the use of English among students and teachers of health sciences, which is a limitation in scientific production, which to some extent may also be a factor that reduces the increase in scientific production [25]. More studies are needed to understand the effects of language on scientific production in Scopus as well as the resources and funding of scientific projects that end up in publication [26]. Our results also show international scientific collaboration, where there are usually formal collaborations in which the institutions or countries sign agreements highlighting the benefits and responsibilities of the study in question; at the same time, there are also informal collaborations, where the scientists involved share all or part of the information, as well as the materials and training necessary to carry out the study [13,14,16].…”
Section: Discussionmentioning
confidence: 99%
“…32 Also, national and international investments in technological innovation has not prioritised substance abuse research in Latin America, even though millions of dollars have been invested in the development of rapid response projects. 4,33,34 As long as health stakeholders, political leaders and clinical practice managers do not highlight substance abuse as part of the scientific priorities in every Latin American country, HCWs will be threatened by substance use without control and prevention measures.…”
Section: Discussionmentioning
confidence: 99%
“…1 Pandemic containment activities have included increasing public spending, prioritising COVID-19, and strengthening health systems in terms of diagnosis, treatment, and monitoring, and developing research and technological innovation. 2-4…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the p-value is not sufficient for clinical interpretation 4 , certain factors (such as effect size and sample size) can undermine the conclusions, resulting in large amounts of bias. One of our limitations was the sample size since in the context of confinement and social distancing it has been difficult for us to voluntarily enroll patients in the study.…”
mentioning
confidence: 99%